Do TFEU provisions on free movement of goods apply to private parties: Expanded vertical or horizontal direct effect? - Savković Vladimir (Anali Pravnog Fakulteta u Beogradu)
The paper aims to establish whether and to what extent the TFEU provisions on free movement of goods apply to legal relations established between two or more private parties. To that end, a stringent analysis of the case law related to this particular issue is provided, aimed at supporting the initial hypotheses that, notwithstanding sporadic but only implicit inclination in its judgments towards establishing the direct horizontal effect of the free movement of goods, the CJEU has constantly and resolutely abstained from recognizing the existence of such an effect - the same effect that it acknowledged decades ago, regarding the free movement of workers and freedom to provide services. Before this analysis, overview is provided of the status quo regarding the horizontal direct effect of the free movement of workers and services, which was needed not only for understanding the differences in the CJEU's approach to various fundamental freedoms but also to outline the general framework in which the horizontal direct effect of fundamental freedoms currently exists, too. Finally, based on the case law analysis, the conclusion is offered that in terms of the recent developments in the field of free movement of goods the CJEU has opted for further expansion of the concept of vertical direct effect in order to both avoid establishing the horizontal direct effect of the freedom of movement of goods and safeguard the functioning of internal market against certain impediments generated by private parties.